The Effective and Efficient Construction of an Endangered Language Preservation: Study Case of Betawi Language - Tarizha Gusti Oktaviani; Iskandarsyah Siregar; Arju Susanto (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
Language is both a product and a very important medium of civilization. This condition makes the role and condition of language very crucial in civilization. Like the Betawi language, which is currently threatened with latent and slow extinction. It is feared that this condition will lead to the loss of Betawi's original values and culture, not its people biologically. This research tries to find an effective and efficient construction in preserving endangered languages. In the case of the Betawi language, an approach that pays attention to the cultural dynamics that occur within the Betawi community is the key to success. The conscientious situation of the Betawi people in loving and being passionate in defending their language is also an absolute requirement in the process of preserving this endangered language.